2010
DOI: 10.1136/qshc.2009.033118
|View full text |Cite
|
Sign up to set email alerts
|

Am I (un)safe here? Chemotherapy patients' perspectives towards engaging in their safety

Abstract: Objectives To assess chemotherapy patients' perceptions of safety and their attitudes towards participating in error-prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 33 publications
5
76
0
Order By: Relevance
“…Information can increase self-efficacy and risk perceptions thereby increasing intention to act (Schwappach & Wernli 2010a), perhaps by giving patients an understanding of what they can do (Smythe, 2010). Clinicians" ability to communicate with patients is important in this respect.…”
Section: Clinician-patient Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Information can increase self-efficacy and risk perceptions thereby increasing intention to act (Schwappach & Wernli 2010a), perhaps by giving patients an understanding of what they can do (Smythe, 2010). Clinicians" ability to communicate with patients is important in this respect.…”
Section: Clinician-patient Relationshipsmentioning
confidence: 99%
“…In contrast, if patients" perceived their role to be that of passive recipient of medical expertise they were unwilling to engage actively with their safety for example by self-management of their condition or by challenge clinicians about their practice (Burnett et al, 2010;Entwistle, 2005;Forsyth, 2000;Hibbard, et al, 2005;Longtin et al, 2009;Manias et al, 2004;Schwappach & Wernli, 2010a). One study found that patients did not read medication instructions (Brown et al, 2006) and others found that patients were reluctant to mark their body to indicate the site of surgery (DiGiovanni et al, 2003;Waterman, 2006) suggesting a submissive attitude towards safety.…”
Section: Cognitive Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived poor care coordination was the single most important risk factor for reporting errors. Similar studies have been conducted to assess the frequency of infection during or after hospital stay or errors in chemotherapy treatment [12][13][14] . Despite the tragedy associated with all these incidents, medical errors also come at high financial cost.…”
Section: Health Care As a Risk: The Magnitude Of The Safety Problemmentioning
confidence: 99%
“…There is recognition amongst healthcare professionals that patients normally feel anxious in the healthcare setting however, the assumption that feeling unsafe is merely the absence of feeling of safety is an easily made, but incorrect, assumption. Patients do not necessarily feel unsafe if errors occur (Schwappach 2010), neither do they necessarily feel safe if all is done to make some so. The recognition of safety as being both a psychological and physical perception is addressed in some, but not all, of the literature (Stenhouse 2013), and the recognition of the role of perceived threat as a subjective perception is not always recognised.…”
Section: Introductionmentioning
confidence: 99%